2004
DOI: 10.1038/sj.onc.1207963
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of caspase-6 and FLIP by the AMPK family member ARK5

Abstract: Colorectal cancer cells are unique in that they escape Fasmediated cell death in the presence of Fas ligand, and we recently reported that AMP-activated protein kinaserelated kinase 5 (ARK5) suppresses cell death signaling mediated by cell death receptor in Akt-dependent manner. In the current study, therefore, we examined whether ARK5 is involved in the escape from Fas-mediated cell death of colorectal cancer cells. Among 10 cell lines, ARK5 mRNA expression was observed in LoVo, SW480, and SW1116 cell lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 33 publications
8
72
1
1
Order By: Relevance
“…Caspase-6 can be inhibited posttranslationally by kinase ARK5 (Suzuki et al 2004). In the colon cancer cell line, SW480, which effectively evades Fas-induced apoptosis, it has been shown that caspase-6 is held inactive by the ARK5 kinase.…”
Section: Caspase-6mentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-6 can be inhibited posttranslationally by kinase ARK5 (Suzuki et al 2004). In the colon cancer cell line, SW480, which effectively evades Fas-induced apoptosis, it has been shown that caspase-6 is held inactive by the ARK5 kinase.…”
Section: Caspase-6mentioning
confidence: 99%
“…Although there are two putative ARK5 sites on capase-6, the kinase appears to phosphorylate Ser257. Mutation of Ser257 to Ala overrides ARK5-mediated inhibition and allows c-FLIP cleavage and apoptosis to proceed in the SW480 cells (Suzuki et al 2004). …”
Section: Caspase-6mentioning
confidence: 99%
“…Caspase-6 differs in several respects from the other executioner caspases. Caspase-6 is much more weakly apoptotic than caspase-3 and -7, although overexpression of caspase-6 does result in apoptosis (2). Caspase-6 also cleaves a different set of cellular substrates (3,4) and displays different substrate specificity against peptide substrates (5).…”
mentioning
confidence: 99%
“…5,27,28 CASP6 activity can furthermore be regulated at both transcriptional and posttranslational levels, including transcriptional initiation, alternate splicing, and phosphorylation events. [29][30][31][32][33] However, it remains unclear which mechanisms are responsible for the increased CASP6 activation in neurodegenerative diseases, such as HD.…”
mentioning
confidence: 99%